2020
DOI: 10.3126/on.v18i1.34239
|View full text |Cite
|
Sign up to set email alerts
|

Fish Assemblage Structure and Environmental Correlates in Nepal’s West Rapti River, Banke

Abstract: The spatial and temporal variations of fish assemblages in rivers and streams of Nepal are poorly understood. So, the present study aimed to explore the spatial and temporal variations of fish assemblage structure in Nepal’s West Rapti River. The data were collected during autumn, winter and spring seasons, from October 2018 to April 2019. Fish samples were collected using cast net of 12 mm mesh size. A total of 28 species belonging to 7 orders, 10 families and 19 genera were recorded during the study. The ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
2
0
0
Order By: Relevance
“…The most diverse order and family sampled were the Cypriniformes and Cyprinidae, respectively. This result is consistent with the findings of several previous studies (Shrestha et al, 2009;Mishra and Baniya, 2016;Shrestha, 2016;Subba et al, 2017;Yadav, 2017;Limbu et al, , 2019aLimbu and Gupta, 2019;Punam and Limbu, 2019;Chaudhary et al, 2020;Limbu and Prasad, 2020;Prasad et al, 2020) and the fact that the majority of freshwater fish are in the order Cypriniformes and family Cyprinidae (Nelson, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…The most diverse order and family sampled were the Cypriniformes and Cyprinidae, respectively. This result is consistent with the findings of several previous studies (Shrestha et al, 2009;Mishra and Baniya, 2016;Shrestha, 2016;Subba et al, 2017;Yadav, 2017;Limbu et al, , 2019aLimbu and Gupta, 2019;Punam and Limbu, 2019;Chaudhary et al, 2020;Limbu and Prasad, 2020;Prasad et al, 2020) and the fact that the majority of freshwater fish are in the order Cypriniformes and family Cyprinidae (Nelson, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study showed that species of fishes belonging to order Cypriniformes were abundant during the winter season at station B, which lies at base of hilly area thus serves as overlapping niche for both warm and cold water fishes. This result matches with the findings by Edds (1986), Chaudhary et al (2020), and Limbu et al (2018aLimbu et al ( , 2018b, which might be due to the same elevation patterns of the rivers investigated and the similar water quality parameters of the rivers. The possible reason could be due to the availability of sufficient volume of water which is comparatively less disturbed as compared to other sites.…”
Section: Discussionsupporting
confidence: 92%